Practical design of ships and other floating structures : proceedings of the 14th International Symposium, PRADS 2019, September 22-26, 2019, Yokohama, Japan.: proceedings of the 14th International Symposium, PRADS 2019, September 22-26, 2019, Yokohama, Japan. Volume III (2021) - Unknown
No abstract available